Reducing Residual Moveout Seismic Anisotropy Model Using Three-Ray GMA (General Moveout Approximation) - Egie Wijaksono; Humbang Purba (Testing Center for Oil and Gas LEMIGAS, 2020)
A â€œ hockey stickâ€ phenomenon is one of anisotropic effects that should be eliminated in marineÂ seismic data. It can increase residual moveout at the far offsets and impact to the distortion of refl ection eventÂ amplitude, eventually, reduce the seismic imaging quality. Conventional hyperbolic moveout approximation, anÂ algorithm isotropic model commonly used for seismic processing, has a drawback in supressing such phenomenon.Â It is also not reliable for medium anisotropy model and long offset data. Many researchers formulated nonhyperbolicÂ moveout approimations but it has limitation analysis for inteval offset-depth ratio (ODR) more thanÂ four. We present three-ray generalized moveout approximation (three-ray GMA) for transversely isotropicÂ medium with vertical axis of symmetry (VTI), which is a modifi ed non-hyperbolic moveout approximation fromÂ original GMA, to cover up of the weakness of the hyperbolic approximation. The objective of this study is toÂ eliminate â€œ hockey stickâ€ effect and minimize the residual moveout much smaller at once at the far offsets (offsetdepthÂ ratio > 4). In this study, we used synthetic data for single layer model in VTI medium to calculate relativeÂ traveltime error for each recent method over a range of offsets (0 â‰¤ ODR â‰¤ 6) and anisotropic parameters (0 â‰¤Â ï¨ â‰¤ 0.5). We also make comparative method for multi layer and implement it in a velocity analysis and residualÂ moveout calculation. The three-ray GMA shows a better capability than comparative method to reduce residualÂ moveout for larger offset. This result is important for enhancing seismic imaging.